Conocimientos, uso y efectos secundarios de la píldora anticonceptiva de emergencia en estudiantes de la Carrera de Medicina Humana - Caraguay Quinde, Clara Alexandra (2020)
The emergency contraceptive pill (ECP), is a contraceptive method used to prevent unwanted pregnancies up to 72 hours after unprotected sexual intercourse or failure of the usual contraceptive method; in recent years its use has been increasing, the lack of knowledge has caused it to be used incorrectly as a regular contraceptive method, without measuring the consequences that its inadequate use implies, it is important to know the current status of this problem, in order to contribution in the design of strategies aimed at improving their knowledge and proper use; it is the reason that the present investigation was proposed with the objective of: Identifying the knowledge, use and side effects of the emergency contraceptive pill in students of the Human Medicine career at the National University of Loja, being a descriptive, quantitative, prospective, cross-sectional study in which 315 students who met the inclusion criteria participated, the results conclude that 77.14% of the students have a high level of knowledge, 4.12% obtained a low level of knowledge; They use the PAE 25.39%; The most frequent side effects predominate: headache in 30%, nausea and dizziness in 22.5%, menstrual spotting 18.75%, a minimum percentage 12.5% showed no symptoms. Therefore, it is concluded that most of the students participating in the study have a high level of knowledge, a quarter of the population has used it. Key Words: Emergency contraceptive pill, knowledge, use, side effects.